2004
DOI: 10.1007/s00253-004-1736-x
|View full text |Cite
|
Sign up to set email alerts
|

Reductive transformation of TNT by Escherichia coli: pathway description

Abstract: The reductive transformation of 2,4,6-trinitrotoluene (TNT) was studied using aerobically grown Escherichia coli cultures. In the absence of an external carbon or energy source, E. coli resting cells transformed TNT to hydroxylaminodinitrotoluenes (2HADNT, 4HADNT, with 4HADNT as the dominant isomer), aminodinitrotoluenes (4ADNT, with sporadic detection of 2ADNT), 2,4-di(hydroxylamino)-6-nitrotoluene (24D(HA)6NT), 2,4-diamino-6-nitrotoluene (24DA6NT), and an additional compound which was tentatively identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
36
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 27 publications
2
36
0
Order By: Relevance
“…These three enzymes, NfsA, NfsB and NemA, which contain the flavin mononucleotide as prostetic group, can reduce up to two nitro groups (-NO 2 − ) from different nitroaromatics compounds as TNT (Esteve-Nuñez et al 2001;Yin et al 2005) to the corresponding amines (-NH 2 ) via hydroxylamino (-NHOH) intermediates. The reduction is catalysed through the addition of one or two electrons from the cofactors NADH and/or NADPH (Roldán et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These three enzymes, NfsA, NfsB and NemA, which contain the flavin mononucleotide as prostetic group, can reduce up to two nitro groups (-NO 2 − ) from different nitroaromatics compounds as TNT (Esteve-Nuñez et al 2001;Yin et al 2005) to the corresponding amines (-NH 2 ) via hydroxylamino (-NHOH) intermediates. The reduction is catalysed through the addition of one or two electrons from the cofactors NADH and/or NADPH (Roldán et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro denitration of TNT with purified NEM reductase was described by Williams et al (21), but the authors did not provide quantitative data with E. coli cells. Also, several reports have described the reduction of TNT by E. coli but not its denitration (6,14,22,23). Only one recent study has mentioned denitration of TNT by E. coli, but no quantitative data were provided and TNT was not the sole nitrogen source (13).…”
mentioning
confidence: 99%
“…Next, ammonium was likely used as a nitrogen source by E. coli via the glutamine synthetase/glutamate synthase pathway (16). The formation of 4-hydroxylamino-2,6-dinitrotoluene as a major intermediate was observed in the enzymatic reduction of TNT with extracts from E. coli (20) and with several enzymes of E. coli (21,22). We observed a greater bacterial growth in the presence of glucose, and we found that more 4-A-2,6-DNT was produced than in the presence of glycerol (Table 1).…”
mentioning
confidence: 99%
“…For instance, some E. coli laboratory strains have multiple enzymes that degrade 2,4,6-trinitrotoluene (TNT) for release of nitrite from the nitroaromatic ring, yielding 2-hydroxylamino-6-nitrotoluene (5). In addition to NemA, both NfsA and NfsB nitroreductases catalyze TNT reduction, converting the nitro groups on the aromatic ring to the corresponding hydroxylamino derivatives (1,17,29). All these nitroreductases degrade toxic nitrous compounds, ultimately releasing ammonium ions that can, in turn, be used as a nitrogen source by E. coli for growth.…”
mentioning
confidence: 99%